Inhibitory effects of a maleimide compound on the virulence factors of Candida albicans - Ying Li; Chaoqun Chen; Liu Cong; Shanshan Mao; Mingzhu Shan; Zibing Han; Jiayi Mao; Zhiyu Xie; Zuobin Zhu (Virulence)
Candidiasis caused by Candida albicans infection has long been a serious human health problem. The pathogenicity of C. albicans is mainly due to its virulence factors, which are novel targets of antifungal drugs for low risk of resistance development. In this study, we identified a maleimide compound [1-(4-methoxyphenyl)-1hydro-pyrrole-2,5-dione, MPD] that exerts effective anti-virulence activity. It could inhibit the process of adhesion, filamentation, and biofilm formation in C. albicans. In addition, it exhibited low cytotoxicity, hemolytic activity, and drug resistance development. Moreover, in Galleria mellonella-C. albicans (in vivo) infection model, the survival time of infected larvae was significantly prolonged under the treatment of MPD. Further, mechanism research revealed that MPD increased farnesol secretion by upregulating the expression of Dpp3. The increased farnesol inhibited the activity of Cdc35, which then decreased the intracellular cAMP content resulting in the inhibition of virulence factors via the Ras1-cAMP-Efg1 pathway. In all, this study evaluated the inhibitory effect of MPD on various virulence factors of C. albicans and identified the underlying mechanisms. This suggests a potential application of MPD to overcome fungal infections in clinics.